'Reverse internationalization' in Chinese firms: a study of how global startup OEMs seek to compete domestically. Issue 2 (2nd April 2016) - Chin, Tachia; Liu, Ren-huai; Yang, Xuemei
Abstract : This research investigates whether the global startup original equipment manufacturers (OEMs) in China could employ their knowledge-acquisition capability developed via internationalization to compete domestically (i.e. reverse internationalization ), facing the recession in developed markets. Results examine that knowledge-acquisition capability can help these firms compete in 'reverse internationalization', while the conduct of own brand strategy partially mediates the positive relationship between their capability and domestic performance. We contribute to the literature by identifying the unique 'Chinese global startup OEMs', recognizing knowledge-acquisition capability as a high-order dynamic capability for such firms, and introducing a novel entrepreneurial phenomenon we call 'reverse internationalization'.